FOSSES: Framework for open‐source software evaluation and selection. (20th February 2019) - Adewumi, Adewole; Misra, Sanjay; Omoregbe, Nicholas; Sanz, Luis Fernandez
Summary: A plethora of approaches exists for the evaluation and selection of open‐source software (OSS) in the literature. However, these approaches are hardly ever used in practice for the following reasons: first, the lack of a situational‐based procedure to define the evaluation criteria for OSS given its varied and dynamic nature; second, the inability of existing evaluation techniques, such as the analytic hierarchy process, to cope well with uncertainty factors, thus producing misleading results that affect the quality of decisions made; and third, a significant number of existing approaches require the prototyping of alternatives being considered in order to facilitate evaluation and decision‐making. This study addresses the aforementioned challenges by evolving a process framework for evaluating and selecting OSS. The proposed framework is validated by applying it to a case study. In addition, expert opinion was elicited via questionnaires from 10 experts, and overall feedback suggests that 80% of them are willing to adopt the approach.